Strangulated Richter’s Hernia in an Indirect Inguinal Hernia - Bouali, Mounir; Falousse, Kabira; El Wassi, Anas; El Bakouri, Abdelilah; El Hattabi, Khalid; Bensardi, Fatima Zahra; Fadil, Abdelaziz (European Scientific Journal, ESJ, 2023)
Introduction: Richter’s hernia is an abdominal hernia in which part of the circumference of the intestine is incarcerated in the hernia sac. Case report: We report a case of Richter’s hernia incarcerated through an indirect inguinal hernia. The patient presented with an occlusive syndrome with an imaging appearance of a right inguinal hernial strangulation bowel obstruction. Surgical exploration revealed the presence of an indirect inguinal Richter’s hernia with a viable bowel. Discussion: Richter’s hernia is a rare hernia of the abdominal wall, it is known by the unusual clinical presentation and the often erroneous late diagnosis that leads to high morbidity and mortality rates. Therefore, with high clinical suspicion, abdominal CT scan is recommended to establish a prompt diagnosis, as timely surgical intervention is important to reduce mortality. Conclusion: Surgery is the basis of its treatment, but prompt surgical intervention remains. Assessment of bowel viability is an essential part of the repair.